Analisis Kesalahan Dalam Menyelesaikan Soal Trigonometri Pada Siswa SMAN 1 Parepare - Fahri Alamsyah (Tautologi: Journal of Mathematics Education, 2023)
This research is a qualitative descriptive research with the aim of determining errors in solving trigonometry problems in class XI social studies 3 students of SMA Negeri 1 Parepare. The subjects of this study were class XI students, especially in class XI social studies 3 and 3 subjects were selected for in-depth analysis related to errors experienced in solving trigonometric problems. Data collection techniques use test-giving techniques and interview techniques. Students are given a test in the form of trigonometry questions. Before use, the question is first tested for validation.After obtaining the research data, the researcher analyzed the research data using triangulation. Data engineering is carried out with the stages of data reduction, data presentation and data verification. The results of this study continue the mistakes experienced by students in solving trigonometry problems including misunderstanding concepts, principle errors and technical errors. The causative factor is the lack of interest in learning mathematics so that it is less thorough in doing the problem, as well as factors from within the student himself and the level of understanding of concepts and prerequisites is lacking.